Factors affecting physician decision-making regarding antiplatelet therapy in minor ischemic stroke - Liu, Tingting; Li, Yanan; Niu, Xiaoyuan; Wang, Yongle; Zhang, Kaili; Fan, Haimei; Ren, Jing; Li, Juan; Fang, Yalan; Li, Xinyi; Wu, Xuemei (Frontiers in Neurology, 2022)
To investigate the most important factors affecting physician decision-making regarding antiplatelet therapy. We retrospectively gathered patients of minor ischemic stroke from 2010 to 2018. The population was divided into four groups: aspirin monotherapy (AM), dual antiplatelet therapy with aspirin and load-clopidogrel (clopidogrel loading dose of 300 mg on the first day, DAPT-ALC), dual antiplatelet therapy with aspirin and unload-clopidogrel (clopidogrel 75 mg daily with no loading dose, DAPT-AUC), and clopidogrel monotherapy (CM). Overall, 1377 of 1494 patients were included in the analysis, and the mean ± SD age was 62.0 ± 12.7) years; 973 (70.7%) patients were male. The four groups were AM (n=541, 39.3%), DAPT-ALC (n =474, 34.4%), DAPT- AUC (n=301, 21.9%), and CM (n=61, 4.4%). The mean age of patients who received antiplatelet monotherapy was higher than that of those who received dual antiplatelet therapy (63.7%-65.7% vs. 59.6%-61.4%), and the median initial systolic blood pressure level was higher in the DAPT-ALC group than in the other groups (all P < 0.05). Compared with AM, patients who age under 75 years old, initial SBP level lower than 180 mmHg, a history of AM, coronary heart disease, no history of intracerebral hemorrhage, stroke onset occurring after guideline recommendations were updated, onset to arrival time within 24 hours, initial NIHSS score ≤ 3 have a higher chance to accept DAPT-ALC. Compared with DAPT-ALC, the choice of DAPT-AUC was associated with an initial SBP level lower than 180 mmHg, a history of smoking, hypertension, no history of ICH, previous treatment with antihypertensives and onset year after the recommendations were updated. Many factors affect the decision-making of doctors regarding antiplatelet therapy, especially guidelines, age, admission SBP level, and hypertensive disease.